2005
DOI: 10.1093/brain/awh445
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Parkinson's disease: loss of dopamine and noradrenaline innervation in the limbic system

Abstract: The reason for the high frequency of depression and anxiety in Parkinson's disease is poorly understood. Degeneration of neurotransmitter systems other than dopamine might play a specific role in the occurrence of these affective disorders. We used [11C]RTI-32 PET, an in vivo marker of both dopamine and noradrenaline transporter binding, to localize differences between depressed and non-depressed patients. We studied eight and 12 Parkinson's disease patients with and without a history of depression matched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
647
5
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 910 publications
(700 citation statements)
references
References 50 publications
24
647
5
10
Order By: Relevance
“…The implication of an extra‐nigrostriatal pathway in the prefrontal, temporal and limbic cortices implies that other neurotransmitters, such as serotonin and noradrenaline, are also implicated in depression in PD 49, 50, 51. This view is supported by studies using PET or SPECT to show that cortical cholinergic activity inversely correlated with depression 12 and changes of serotonin or noradrenaline in PD patients with depression, compared to HCs or PD patients without depression 11, 13, 16, 17, 18, in addition to dopaminergic alterations 19, 20, 21, 22, 26, 27. Although it is challenging to identify a unifying model of neuropathology of depression in PD, these observations suggest that depression is unlikely to be the result of a single brain region or neurotransmitter system but involves the dysregulation of cortico‐limbic networks in addition to that of the nigrostriatal pathway.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The implication of an extra‐nigrostriatal pathway in the prefrontal, temporal and limbic cortices implies that other neurotransmitters, such as serotonin and noradrenaline, are also implicated in depression in PD 49, 50, 51. This view is supported by studies using PET or SPECT to show that cortical cholinergic activity inversely correlated with depression 12 and changes of serotonin or noradrenaline in PD patients with depression, compared to HCs or PD patients without depression 11, 13, 16, 17, 18, in addition to dopaminergic alterations 19, 20, 21, 22, 26, 27. Although it is challenging to identify a unifying model of neuropathology of depression in PD, these observations suggest that depression is unlikely to be the result of a single brain region or neurotransmitter system but involves the dysregulation of cortico‐limbic networks in addition to that of the nigrostriatal pathway.…”
Section: Methodsmentioning
confidence: 95%
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 11 imaging studies that have explored the neural bases of PD patients with and without depression using different imaging techniques [91][92][93][94][95][96][97][98][99][100][101] (See table 4). Among these studies, there is only one study that found no differences in brain regions between PD patients with and without depression [97] (In this study patients had mild to severe disease stages, average disease duration was 4.9 years and age at onset was 62.6).…”
Section: Depressionmentioning
confidence: 99%
“…In addition, using radiotracers other than the classical 18 F-DOPA, PET can also identify alterations in other catecholaminergic neurotransmitter systems and demonstrate that depression and anxiety in the patients is correlated with specific loss of DA and noradrenergic innervation in the limbic system [95].…”
Section: Applications Of Pet In Neurodegenerative Statesmentioning
confidence: 99%